Equivalência assintótica forte e fraca de germes de funções semi-algébricas contínuas na origem e no infinito - Sousa, Roger Oliveira (2022)
In this work we present the notions ofweak and strong asymptotic equivalences at the origin and at infinity for germs os semi-algebraic and continuous functions in the real punctured plane. We show that such equivalences are completely determined and characterizad by an adapted finite combinatorial object, called minimal pizza associated with the corresponding germ of considered function.